Long-Term Release of Dexamethasone With a Polycaprolactone-Coated Electrode Alleviates Fibrosis in Cochlear Implantation - Chen, Dongxiu; Luo, Yanjing; Pan, Jing; Chen, Anning; Ma, Dong; Xu, Muqing; Tang, Jie; Zhang, Hongzheng (Frontiers in Cell and Developmental Biology, 2021)
Cochlear implantation (CI) is the major treatment for severe sensorineural hearing loss. However, the fibrotic tissue forming around the electrodes reduces the treatment effectiveness of CI. Dexamethasone (DEX) is usually applied routinely in perioperative treatment of cochlear implantation (CI), but its diffusion in the inner ear after systemic administration is limited. In the present study, an electrode coated with polycaprolactone (PCL) loaded with dexamethasone was developed with a simple preparation process to maintain the stability of the electrode itself. The DEX-loaded PCL coating has good biocompatibility and does not change the smoothness, flexibility, or compliance of the implant electrode. Stable and effective DEX concentrations were maintained for more than 9 months. Compared with the pristine electrode, decreasing intracochlear fibrosis, protection of hair cells and spiral ganglion cells, and better residual hearing were observed five weeks after PCL-DEX electrode implantation. The PCL-DEX electrode has great potential in preventing hearing loss and fibrosis by regulating macrophages and inhibiting the expression of the fibrosis-related factors IL-1β, TNF-α, IL-4, and TGF-β1. In conclusion, the PCL-DEX electrode coating shows promising application in CI surgery.